2022
DOI: 10.7554/elife.75894
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mapping of keratin networks in 3D

Abstract: Mechanobiology requires precise quantitative information on processes taking place in specific 3D microenvironments. Connecting the abundance of microscopical, molecular, biochemical and cell mechanical data with defined topologies has turned out to be extremely difficult. Establishing such structural and functional 3D maps needed for biophysical modeling is a particular challenge for the cytoskeleton, which consists of long and interwoven filamentous polymers coordinating subcellular processes and interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…The observations indicate that laminin-332 enhances the persistence of cell migration and mandate the investigation of KF network organization at subcellular resolution. The speed of image recording was, however, not fast enough to obtain image stacks, which would allow satisfactory resolution of single KFs or KF bundles in the motile cells and therefore prevented detailed network analyses using previously described image analysis techniques ( Windoffer et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The observations indicate that laminin-332 enhances the persistence of cell migration and mandate the investigation of KF network organization at subcellular resolution. The speed of image recording was, however, not fast enough to obtain image stacks, which would allow satisfactory resolution of single KFs or KF bundles in the motile cells and therefore prevented detailed network analyses using previously described image analysis techniques ( Windoffer et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the restoration model was further validated by comparing the results of network extraction from the raw and processed images using TSOAX and KerNet ( Figure 3 ; cf. ( Windoffer et al, 2022 )], which showed a significant improvement on the resemblance of the model with the original network structure. The trained CARE model ( Supplementary File S1 ) was henceforth used on all keratin network images prior to their segmentation analysis for the extraction of KF properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in microscopy and image analysis have provided transformative insight into the three-dimensional (3D) architecture of cellular components in tissues, organs and entire organisms. Now, in eLife, Rudolf Leube and colleagues at RWTH Aachen University – including Reinhard Windoffer as first author – report on new insights into networks of intermediate filaments in three different types of epithelial cells ( Windoffer et al, 2022 ).…”
mentioning
confidence: 99%